2020
DOI: 10.1111/aogs.13958
|View full text |Cite
|
Sign up to set email alerts
|

Role of prenatal magnetic resonance imaging in fetuses with isolated agenesis of corpus callosum in the era of fetal neurosonography: A systematic review and meta‐analysis

Abstract: Introduction Corpus callosum agenesis (ACC) is frequently diagnosed during fetal life; its prognosis depends also on additional anomalies. The additional value of fetal magnetic resonance imaging (MRI) in fetuses with “isolated” complete (cACC) and partial (pACC) agenesis of the corpus callosum on ultrasound is still debated. Material and methods We performed a systematic literature review and meta‐analysis including fetuses with a prenatal diagnosis of cACC and pACC without associated structural anomalies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…In a recent systematic review, we reported that, among fetuses with isolated agenesis of the CC (ACC), the rate of associated anomalies detected exclusively on fetal MRI was lower when neurosonography was performed (5.7%), when compared with the basic assessment of fetal brain (18.5%) 13 . However, the small sample size of the included studies and the heterogeneity of gestational age (GA) at ultrasound and MRI assessments, type and time of follow-up make the results of this systematic review difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, we reported that, among fetuses with isolated agenesis of the CC (ACC), the rate of associated anomalies detected exclusively on fetal MRI was lower when neurosonography was performed (5.7%), when compared with the basic assessment of fetal brain (18.5%) 13 . However, the small sample size of the included studies and the heterogeneity of gestational age (GA) at ultrasound and MRI assessments, type and time of follow-up make the results of this systematic review difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%
“…По данным ряда авторов, применение МРТ позволяет повысить эффективность пренатальной диагностики среди всех аномалий головного мозга плода на 16% [8] и определиться с прогнозом в 20% уже диагностированных случаев [9]. Кортикальные мальформации и аномалии задней черепной ямки являются одними из наиболее распространенных пороков, которые диагностируются по данным пренатальной МРТ, что подтверждает решающую роль метода в определении прогноза в указанных случаях [10]. В нашем исследовании применение пренатальной МРТ при оценке аномалий развития конечного мозга в 9,5% (2/21) случаев позволило получить дополнительные данные, у 14,3% (…”
Section: резюме _____________________________________________________...unclassified
“…A thorough multiplanar ultrasound assessment of the fetal brain according to International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) guidelines 2 is paramount either in cases of an isolated anomaly [3][4][5] or in fetuses at high risk of brain injury, as described by van der Knoop et al 1 . However, there are a few issues that we believe should always be taken into account when discussing the role of neurosonography and fetal MRI in fetuses at risk for brain abnormalities.…”
Section: Moving Beyond the Diatribe On Ultrasound Vs Mrimentioning
confidence: 99%
“…A thorough multiplanar ultrasound assessment of the fetal brain according to International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) guidelines 2 is paramount either in cases of an isolated anomaly 3–5 or in fetuses at high risk of brain injury, as described by van der Knoop et al 1 …”
mentioning
confidence: 99%